10
Пошаговое объяснение:
(4 - 2/3) : (1 3/5 - 1/10) * (1 1/3 + 2 2/2 + 1/6)
считаем первую скобку
4 - 2/3 = 3 3/3 - 2/3 = 3 1/3
вторую скобку
1 3/5 - 1/10 = 1 6/10 - 1/10 = 1 5/10
третью скобку
1 1/3 + 2 2/2 + 1/6 = 1 2/6 + 2 6/6 + 1/6 = 3 9/6 = 4 3/6
теперь делим
3 1/3 : 1 5/10 = 10/3 : 15/10 = 10/3 * 10/15 = 20/9
и умножаем
20/9 * 4 3/6 = 20/9 * 27/6 = 30/3 = 10
10
Пошаговое объяснение:
(4 - 2/3) : (1 3/5 - 1/10) * (1 1/3 + 2 2/2 + 1/6)
считаем первую скобку
4 - 2/3 = 3 3/3 - 2/3 = 3 1/3
вторую скобку
1 3/5 - 1/10 = 1 6/10 - 1/10 = 1 5/10
третью скобку
1 1/3 + 2 2/2 + 1/6 = 1 2/6 + 2 6/6 + 1/6 = 3 9/6 = 4 3/6
теперь делим
3 1/3 : 1 5/10 = 10/3 : 15/10 = 10/3 * 10/15 = 20/9
и умножаем
20/9 * 4 3/6 = 20/9 * 27/6 = 30/3 = 10